Implementasi Nilai-Nilai Pancasila dan Agama dalam Mengantisipasi Kenakalan Remaja di Kota Medan (Studi Kasus di Jalan Marendal Pasar 6 Harjo Sari II Medan Marendal) - Adella, Tri Dini; Asmira, Amanda; Pebiola, Andini Lisa; Lubis, Ayira Nurfadillah; Siregar, Khayla Aulia; Manik, Tsurayya Munira; Hanafi, Sabrian; Abdillah, Yuda; Aulia, Rey Ichsan; Harahap, , M. Husein; Adiguna, Sadar Putra; Harahap, Sahrul Bakti (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Juvenile delinquency on Jalan Marendal Pasar 6 Harjo Sari often becomes a problem that disturbs local residents so that local residents are very wary of crimes committed by local teenagers, one of the crimes being theft at people's homes and so on. This research aims to obtain information related to juvenile delinquency that occurs in the Marendal Pasar 6 area, and understand the causes, impacts, and efforts that have been made by the community or the authorities in dealing with this problem. The research method used is a qualitative approach by collecting information through interviews, observation and literature study. The results of this research show that juvenile delinquency in Marendal Pasar 6 is still a quite serious problem. The main influencing factors are lack of family supervision, bad relationships, and lack of positive activities for teenagers. Although there have been several efforts to address this problem, better cooperation between families, communities and authorities is needed to create an environment that is more conducive to adolescent development.